Synthesis of low-coordinate m-terphenyl metal complexes: structural, electronic and magnetic studies - Valentine, Andrew (2020)
This work aims to expand the library of low-coordinate m-terphenyl metal complexes suitable for electronic investigation. Herein, the synthesis of a series of para-substituted m-terphenyl ligands is reported, featuring a range of different electron-donating and -withdrawing groups. The effects of ligand architecture are then studied with respect to the structural, electronic and magnetic properties of the metal complexes.